2021
DOI: 10.3390/ijms22073499
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Detection of Antibiotic and Multi-Drug Resistant Salmonella: An Update

Abstract: Antibiotic and multi-drug resistant (MDR) Salmonella poses a significant threat to public health due to its ability to colonize animals (cold and warm-blooded) and contaminate freshwater supplies. Monitoring antibiotic resistant Salmonella is traditionally costly, involving the application of phenotypic and genotypic tests over several days. However, with the introduction of cheaper semi-automated devices in the last decade, strain detection and identification times have significantly fallen. This, in turn, ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 99 publications
0
15
0
Order By: Relevance
“…Over the past decades, the improper and uncontrolled use of antibiotics has allowed the appearance of strains of Salmonella with multiple drug resistance in many countries (Ben Salem et al, 2012;Nacer et al, 2022;Samy et al, 2022). For that reason, the antimicrobial resistance of Salmonella has become a matter of concern worldwide due to the significant threat that can present to public health (Wu and Hulme, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decades, the improper and uncontrolled use of antibiotics has allowed the appearance of strains of Salmonella with multiple drug resistance in many countries (Ben Salem et al, 2012;Nacer et al, 2022;Samy et al, 2022). For that reason, the antimicrobial resistance of Salmonella has become a matter of concern worldwide due to the significant threat that can present to public health (Wu and Hulme, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Comparative testing applied to numerous types of foodstuff seeded with Salmonella serotypes has demonstrated that the MIOOOS is as proficient as conventional culture systems. This method has received preliminary AOAC approval for recognizing Salmonella serotypes in all types of foodstuff (S. Wu & Hulme, 2021). Bioluminescence method has probably been applied most often in foodstuff evaluation to recognize bacterial adenosine triphosphate (ATP).…”
Section: Physicochemical Assaysmentioning
confidence: 99%
“…319 Human infections are generally due to the ingestion of contaminated food or water and can generally be attributed to four key serovars: S. Typhi and S. Paratyphi (Typhoidal Salmonellae), the causative agents of typhoid and paratyphoid fever, and S. Typhymurium and S. Enteritidis (non-typhoidal Salmonellae, NTS), responsible for gastroenteritis and bloodstream infections. 320,321 Conventionally, Salmonella infections are treated with antibiotics, but the rise of multidrug-resistant strains demands the development of effective vaccines. 322 Figure 15.…”
Section: Salmonella Entericamentioning
confidence: 99%
“…Typhymurium and S . Enteritidis (non-typhoidal Salmonellae, NTS), responsible for gastroenteritis and bloodstream infections. , Conventionally, Salmonella infections are treated with antibiotics, but the rise of multidrug-resistant strains demands the development of effective vaccines …”
Section: Emerging Amr Targetsmentioning
confidence: 99%